Balancing Cadence and Flow: Evaluating Agile Frameworks for Optimal Software Delivery Outcomes - Yuni T, Veronika (Digitus : Journal of Computer Science Applications, 2024)
This study compares the impacts of Scrum and Kanban on software quality, team sustainability, and project predictability within Agile project management. As Agile adoption expands across industries, organizations face the challenge of selecting methods that fit their operational needs and team dynamics. By drawing on empirical case studies and literature, this research highlights the practical differences between Scrum’s cadence-based framework and Kanban’s flow-based model. A comparative analysis was conducted using data from major implementations (e.g., Adobe, John Deere, BBC Worldwide), supported by Agile maturity studies and academic evaluations. Metrics examined include defect reduction, cycle time, velocity stability, lead time, and team stress levels. Scrum demonstrated strong outcomes in early-stage quality improvement and structured delivery. Kanban, in contrast, offered stronger long-term flow consistency and fewer customer-reported defects. Furthermore, hybrid approaches such as Scrumban emerged as practical alternatives that balance predictability with adaptability. Results indicate that both frameworks yield significant benefits when implemented with high team autonomy and cultural alignment. While Scrum enhances predictability through time boxed sprints, Kanban facilitates flexibility and continuous delivery. The study highlights the critical role of implementation quality and Agile maturity in determining success. In conclusion, method choice should reflect organizational context, with growing support for hybrid adoption. This research provides actionable insights for Agile teams and decision makers seeking to align methodology with project goals, workforce dynamics, and customer expectations.